2008
DOI: 10.1194/jlr.m700401-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

SMS overexpression and knockdown: impact on cellular sphingomyelin and diacylglycerol metabolism, and cell apoptosis

Abstract: Sphingomyelin synthase (SMS), the last enzyme in the sphingomyelin (SM) biosynthetic pathway, uses ceramide and phosphatidylcholine as substrates to produce SM and diacylglycerol (DAG). To evaluate the role of SMS in apoptosis, we generated Chinese hamster ovary cells that stably express human SMS1 or SMS2. We found that SMS1 or SMS2 overexpression results in a significant increase in cellular levels of SM (24% or 20%) and DAG (35% or 31%), respectively, compared with controls. Cells overexpressing SMS1 or SMS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
71
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(79 citation statements)
references
References 48 publications
7
71
1
Order By: Relevance
“…These observations complement the fact that over-expression of SMS1 or SMS2 in Chinese hamster ovary (CHO) cells increased the number of detergent-insoluble microdomains and TNF-induced apoptosis. 77 In both the SMS2 KO macrophages and HEK 293 cells, NF-gB activation was one of the down-stream signaling events that were inhibited upon loss or down-regulation of SMS2, thus supporting an early report in which a link between stimulation of SM synthesis and nuclear translocation of NF-gB was established. 78 SMS1 has been also implicated in raft-dependent activation of T-cell receptor in Jurkat cells.…”
Section: Sms1 and Sms2 As Regulators Of Sm Homeostasis And Receptor-msupporting
confidence: 57%
See 3 more Smart Citations
“…These observations complement the fact that over-expression of SMS1 or SMS2 in Chinese hamster ovary (CHO) cells increased the number of detergent-insoluble microdomains and TNF-induced apoptosis. 77 In both the SMS2 KO macrophages and HEK 293 cells, NF-gB activation was one of the down-stream signaling events that were inhibited upon loss or down-regulation of SMS2, thus supporting an early report in which a link between stimulation of SM synthesis and nuclear translocation of NF-gB was established. 78 SMS1 has been also implicated in raft-dependent activation of T-cell receptor in Jurkat cells.…”
Section: Sms1 and Sms2 As Regulators Of Sm Homeostasis And Receptor-msupporting
confidence: 57%
“…77 An increase of ceramide levels was also observed upon down-regulation of either SMS1 or SMS2 in HeLa and Huh cells, 66,72,74 suggesting that changes in ceramide levels due to modulation of SMSs might be differently regulated depending on the specific cellular context.…”
Section: Sms1 and Sms2 As Regulators Of Lipid-based Signalingmentioning
confidence: 93%
See 2 more Smart Citations
“…Regarding the role of SMS in cell death, some studies reported that downregulation of SMS1 confers resistance to stress-induced apoptosis [40,41].…”
Section: Page 17 Of 43mentioning
confidence: 99%